Clinical features of heart failure with reduced ejection fraction in patients with obstructive sleep apnea syndrome - Andreieva, Iana; Myrnyi, Dmitro; Surmilo, Mikolay; Riznyk, Olha (ScienceRise: Medical Science, 2019)
Aim of the research: to estimate the clinical features of chronic heart failure with a reduced ejection fraction in patients with obstructive sleep apnea compared with patients without sleep breathing disorders and to establish the relationships of clinical symptoms, anthropometric dates with the degree of hypoxic disorders during sleep. Materials and methods. 152 patients with chronic heart failure were enrolled in our open, prospective, non-randomized study. The control group consisted of 57 patients with obstructive sleep apnea without heart failure. A general clinical examination, anthropometric measurements, questionnaires, cardio-respiratory monitoring, echocardiography, the assessment of NT-proBNP were conducted to all participants in the study. Results. Patients from main group compared with control group were older (by 15.6 %, p<0.05), had a higher body mass index and degree of obesity (by 16,9 %, p<0.05 and 22.1 %, p<0,05), had a longer history of arterial hypertension (by 36.3 %, p<0.01), ischemic heart disease (by 23.6 %, p>0.05), AF (by 16.0 %, p>0.05), diabetes (by 25.3 %, p<0.003). According results of correlation analysis in patients with heart failure and obstructive apnea a significant negative relationship apnea-hypopnea index with age (r=–0.418; p<0.001), ejection fraction (r=–0.376; p<0.01) and a direct link with body mass index (r=+0.512; p<0.003) were found. Mean SaO2 significantly correlated with ejection fraction (r=–0.212; p<0.05), duration of arterial hypertension (r=–0.417; p<0.001), the level of office systolic arterial pressure (r=–0.351; p<0.01) and the level of office diastolic arterial pressure (r=–0.331; p<0.01). Conclusions. The prevalence of obstructive sleep apnea in patients with heart failure with reduced ejection fraction is 40.1 %, while 55.7 % of patients have severe obstructive sleep apnea. Patients with heart failure with reduced ejection fraction and obstructive sleep apnea are older, have a higher body mass index; they more often have comorbid pathologies in their medical history, namely, arterial hypertension, coronary heart disease, atrium fibrillation, and diabetes mellitus. According results of a correlation analysis, a significant relationships of apnea-hypopnea index with age (r=–0.418; p<0.001), ejection fraction (r=–0.376; p<0.01) and body mass index (r=+0.512 p<0.003) were found